Reflexivity of Discomfort in Insider-Outsider Educational Research - Hamdan, Amani (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis paper discusses my position as an Arab Muslim woman researcher who is affiliated with a Western university, researching Arab Muslim Canadian women. I discuss how reflexivity has emerged as an element of my research endeavours. Various notions of reflexivity in educational research have been expressed in the literature, yet I focus on what it means to me as an insider-outsider researcher and how it characterizes my research endeavours. In this paper, I explore the complexity of occupying these multiple subjectivities.